Screening and identification of lncRNAs as potential biomarkers for pulmonary tuberculosis. Issue 1 (December 2017) - Chen, Zhong-liang; Wei, Li-Liang; Shi, Li-Ying; Li, Meng; Jiang, Ting-Ting; Chen, Jing; Liu, Chang-Ming; Yang, Su; Tu, Hui-hui; Hu, Yu-ting; Gan, Lin; Mao, Lian-Gen; et al.
Abstract Pulmonary tuberculosis (TB) is among the diseases with the highest morbidity and mortality worldwide. Effective diagnostic methods for TB are lacking. In this study, we investigated long non-coding RNAs (lncRNAs) in plasma using microarray and the potential diagnostic value of lncRNAs for TB. We found a total of 163 up-regulated lncRNAs and 348 down-regulated lncRNAs. Gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and coding-noncoding co-expression (CNC) analyses showed that functions of differentially expressed lncRNAs were mainly enriched in the regulation of alpha-beta T cell activation and the T cell receptor signalling pathway. Four differentially expressed lncRNAs, NR_038221 (fold change = 3.79, P < 0.01), NR_003142 (fold change = 1.69, P < 0.05), ENST00000570366 (fold change = 3.04, P < 0.05), and ENST00000422183 (fold change = 2.11, P < 0.001), were verified using RT-qPCR. Among those, NR_038221, NR_003142, and ENST00000570366 were found to be up-regulated, while ENST00000422183 was down-regulated. The value of the area under the curve (AUC) for the diagnostic model consisting of the four lncRNAs was 0.845 (sensitivity = 79.2%, specificity = 75%). We further predicted 85 mRNAs and 404 miRNAs that potentially interact with these lncRNAs. Our study revealed the potential value of lncRNAs as biomarkers for early diagnosis of TB and the underlying mechanisms of these abnormally expressed lncRNAs in the pathogenesis of TB.